PERANAN KEBIJAKAN NEGARA TERHADAP PERLINDUNGAN HUTAN UNTUK MENEKAN LAJU DEFORESTASI TAMAN NASIONAL TESSO NILO - Manurung, Arifin A.R.; Sulaeman, Rudianda; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Tesso Nilo National Park is a nature conservation are a which was established in 2004, located in Riau Province. The National Park has experienced deforestation of 4.813,9 ha/year period from 2004 to 2013.The resolution mechanism of deforestation which happen comprehensively in National Park Tesso Nilo, one of them is by applying the forest protection policies. Since the function of the National Park as a life support system protection, preservation of biological diversity, sustainable use of natural resouces and ecosystems. The purpose of this study is to determine the role of state policy in reducing the rate of deforestation and identify contributing factors in Tesso Nilo. Methods of data collection were documentation, interview and quesitionnaires. The sampling techniques were purposive and quoted sampling. The total sample of this research were 25 peoples, 2 persons from Hall of National Park Tesso Nilo, 2 persons from non-govermental organization, one person from Forestry Service and 20 local peoples around National Park Tesso Nilo. The data obtained, processed using technique percentage and arranged in the form of tables, so it can be deduced. The results showed the implementation of state policy in Tesso Nilo has small role in reducing deforestation, this is due to lack of socialization to the community. In justice to the surrounding community, lack of socialization and law enforcement, lack of infrastructure, unleashing the spread of palm oil fruit from the region have became the caused of deforestation in Tesso Nilo. Keyword : Policy, Deforestation, National Park